(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To characterize the epidemiological clinical profile of children with ostomies treated in the outpatient clinic of a reference public teaching hospital for children in Brazil. Method: Descriptive, documentary, retrospective and quantitative study, carried out by extracting sociodemographic and clinical data from electronic medical records of children with ostomies, monitored from 2014 to 2018. The data underwent descriptive statistics, and in the analysis, the data were organized in a spreadsheet in Microsoft Excel version 2010, distributed in three tables, their values represented in absolute and relative frequency. Results: Of the 85 children with ostomy, there was a predominance of males, aged between 1 and 4 years. Anorectal anomaly was considered the main diagnosis. There was a high number of colostomies made. Contact dermatitis was the most frequent peristomal complication. There were difficulties in the routine of families attending the outpatient clinic, and the mother as the main caregiver. Conclusion: The study found relevant aspects related to care planning based on the demand of each child and health education for the prevention of complications, essential actions in the provision of safe and quality nursing care, as well as favoring the operationalization of public policies related to the health of children with ostomies.